Difference between revisions of "TrigSimplify Command"

From GeoGebra Manual
Jump to: navigation, search
m (style: bulletted list)
Line 4: Line 4:
 
:Simplifies the given trigonometric Expression.
 
:Simplifies the given trigonometric Expression.
 
:{{examples|1=<div>
 
:{{examples|1=<div>
::<code>TrigSimplify[1 - sin(x)^2]</code> gives ''-sin²(x)+1''.
+
:*<code>TrigSimplify[1 - sin(x)^2]</code> gives ''-sin²(x)+1''.
::<code>TrigSimplify[sin(x)^2 - cos(x)^2 + 1]</code> gives ''2 sin²(x)''.</div>}}
+
:*<code>TrigSimplify[sin(x)^2 - cos(x)^2 + 1]</code> gives ''2 sin²(x)''.</div>}}
 
==CAS Syntax==
 
==CAS Syntax==
 
;TrigSimplify[ <Expression> ]
 
;TrigSimplify[ <Expression> ]
 
:Simplifies the given trigonometric Expression.
 
:Simplifies the given trigonometric Expression.
 
:{{examples|1=<div>
 
:{{examples|1=<div>
::<code>TrigSimplify[1 - sin(x)^2]</code> gives ''cos²(x)''
+
:*<code>TrigSimplify[1 - sin(x)^2]</code> gives ''cos²(x)''
::<code>TrigSimplify[sin(x)^2 - cos(x)^2 + 1]</code> gives ''2 sin²(x)''.</div>}}
+
:*<code>TrigSimplify[sin(x)^2 - cos(x)^2 + 1]</code> gives ''2 sin²(x)''.</div>}}
:{{note|1=<div> This command works for the variable ''x'' only! (<code>TrigSimplify[1 - sin(y)^2]</code> gives ''-sin²(y) + 1''.)</div>}}
+
{{note|1=<div>  
{{note|1=<div> See also [[TrigExpand Command]] and [[TrigCombine Command]].</div>}}
+
:* This command works for the variable ''x'' only! (<code>TrigSimplify[1 - sin(y)^2]</code> gives ''-sin²(y) + 1''.)
 +
:* See also [[TrigExpand Command]] and [[TrigCombine Command]].</div>}}

Revision as of 20:19, 19 December 2012


TrigSimplify[ <Expression> ]
Simplifies the given trigonometric Expression.
Examples:
  • TrigSimplify[1 - sin(x)^2] gives -sin²(x)+1.
  • TrigSimplify[sin(x)^2 - cos(x)^2 + 1] gives 2 sin²(x).

CAS Syntax

TrigSimplify[ <Expression> ]
Simplifies the given trigonometric Expression.
Examples:
  • TrigSimplify[1 - sin(x)^2] gives cos²(x)
  • TrigSimplify[sin(x)^2 - cos(x)^2 + 1] gives 2 sin²(x).
Note:
© 2021 International GeoGebra Institute